Measuring the perception of safety among Taiwan construction managers - Chen, Wei Tong; Lu, Chun Sheng; Liu, Shu-Shun; Wang, Min-Shun (Journal of Civil Engineering and Management, 2013)
Using Statistical Package for the Social Science (SPSS) and Structural Equation Modeling (SEM), this study develops a model to evaluate construction managers’ perception of safety as relates to six aspects: human error (HE), safety resource and application (SRA), safety equipment and training (SET), site culture and external factors (SCF), safety inspection and audit (SIA), and accident medium and activities (AMA). The model was used to identify and compare the level of safety perceived by Taiwanese construction managers including safety managers, contractor managers, public works managers, design and audit managers, owner audit and control managers, and others. Analysis reveals that safety managers have the highest perception of safety while owner audit and control managers have the lowest. Surprisingly, public works managers and design and audit managers have lower levels of perceived safety than do contractor managers. Apparently, reinforcing the perception of safety between these two types of construction personnel is important to reducing construction accidents in Taiwan.